Norwegian and International Yields in the 10 Year Segment - Sigbjørn Atle Berg (Norges Bank, 2016)
We investigate the relationship between the Norwegian 10 year Treasury yield and the corresponding yields in the major international markets, using both quarterly and monthly data. We find that the Norwegian yield is highly correlated with the EUR, USD and GBP yields. In recent years the correlation with the EUR yields has been stronger than correlations with the USD and GBP yields. We estimate error correction models for the difference between the Norwegian and the international yields. We establish that co-integrating relationships exist, but also that the convergence towards international yields is relatively slow. We test for the short term influence of macro variables on the yield difference and find some weak evidence that economic growth differences and unemployment differences are important, together with the price of oil.
hdl:11250/2506543
Keywords: 330